2021
DOI: 10.1016/j.scr.2021.102415
|View full text |Cite|
|
Sign up to set email alerts
|

Generation of a homozygous knock-in human embryonic stem cell line expressing SNAP-tagged SOD1

Abstract: Superoxide Dismutase 1 (SOD1) is an antioxidant enzyme that protects the cells from radical oxygen species. To study the behavior of endogenous SOD1 under a microscope, we genetically modified H1 human embryonic stem cells (hESCs) to express SOD1 fused with a SNAP-tag, a protein tag that can be covalently labeled with a variety of synthetic probes. The engineered homozygous clone expressing SOD1-SNAP fusion proteins has normal stem cell morphology and karyotype, expresses pluripotency markers, and can be diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Recent progress of human embryonic stem cells (hESCs)/inducible pluripotent stem cell (iPSC)-derived neurons have shown that they can faithfully recapitulate an individual's idiosyncratic neural development. Generations of knock-in stem cell lines expressing fluorophore-tagged Cu-binding proteins could provide an ideal platform for studying the causality of the mutations of diseases [ 236 , 237 ]. Furthermore, the recent advance in super-resolution microscopy enables researchers to approach biophysical problems like protein kinetics and oligomeric states from a single-molecule perspective.…”
Section: Conclusion Remarks and Perspectivesmentioning
confidence: 99%
“…Recent progress of human embryonic stem cells (hESCs)/inducible pluripotent stem cell (iPSC)-derived neurons have shown that they can faithfully recapitulate an individual's idiosyncratic neural development. Generations of knock-in stem cell lines expressing fluorophore-tagged Cu-binding proteins could provide an ideal platform for studying the causality of the mutations of diseases [ 236 , 237 ]. Furthermore, the recent advance in super-resolution microscopy enables researchers to approach biophysical problems like protein kinetics and oligomeric states from a single-molecule perspective.…”
Section: Conclusion Remarks and Perspectivesmentioning
confidence: 99%
“…(ii) What key redox-sensitive residues induce structural changes leading to different SOD1 oligomeric stoichiometries? One may address these questions by combing super-resolution microscopy, organelle-specific sensor, and non-targeted proteomics to investigate SOD1 behaviors in homozygous knocked-in lines . This will provide physiologically relevant information on where SOD1 modulates its oligomeric state, what local oxidative stress is, and how post-translational modifications may be responsible for the shifts between different SOD1 oligomers.…”
Section: Discussionmentioning
confidence: 99%
“…H1 hESCs were cultured as previously described ( Huang et al, 2021 ; Wen et al, 2019 ). Accutase was used for cell detachment, and ROCK-inhibitor was added on the day of cell attachment.…”
Section: Methodsmentioning
confidence: 99%